Evaluation of Cardiovascular Biomarkers and Lipid Regulation in Lactation Friesian Holstein at Different Altitude in West Java, Indonesia - Ujang Hidayat Tanuwiria; Iin Susilawati; Didin Tasripin; Lia Budimulyati Salman; Andi Mushawwir (HAYATI Journal of Biosciences, 2022)
Altitude contributes and plays an important role in the development dairy cows in Indonesia. Altitude is directly related to temperature and humidity, both of which affect cardiovascular function and energy metabolism in dairy cattle. The 120 samples, consisted of 4th-5th lactation Friesian Holstein dairy cows were used in this study. The 40 samples of cattle each spread in three maintenance sites with different altitudes, namely 300 to 500 m above sea level (a.s.l.); 600-900 m a.s.l. and >1,000 m a.s.l. All the study sites located in West Java, Indonesia, to study the effect of altitude on the cardiovascular biomarker and lipid regulation in the dairy cow. Based on the result in this experiment showed that the CRP high sensitivity, H-FABP, homocysteine, and γ-Glutamyl Transpeptidase in Frisian Holstein dairy cows expressed higher levels (P <0.05) at low altitude site (300-500 m a.s.l.) than dairy cows at altitude sites higher (600-900 and >1,000 m a.s.l.), These results indicated, these compounds can be biomarkers for cardiovascular function. This study also showed, the lipid regulation also showed higher levels (P <0.05) at low altitude sites than altitude sites higher.